Diabetes Risk Score of Adult Applications to Primary Health Care Center: A Cross-Sectional Study - Evcimen, Hasan; Ayyıldız, Neşe İşcan; Doğan, Ufuk (Van Yuzuncu Yıl University, 2023)
Objective: Diabetes is a serious public health problem that has increased in frequency in recent years. The aim of this study is to determine the diabetes risk scores of individuals who apply to a primary health care institution. Material-method: This descriptive and cross-sectional study was conducted with 982 individuals between 01.12.2021 and 12.03.2022. Data were collected from the sociodemographic characteristics questionnaire and the Finnish Diabetes Risk Score (FINDRISC) questionnaire. Those with a diabetes risk score of 15 or higher were considered high risk. Results: The mean age of the individuals participating in the study was 37.93±8.63. The mean FINDRISC score of the participants was 8.52±6.83 and 22.8% of them were in the high-risk group. The women included in the study, those who are married, have a low education level, have a low income, have a high BMI, do not exercise, and have a family history of diabetes have a higher risk of diabetes. Conclusion: Approximately one in four people in the study appear to be at high risk. Primary health care institutions need to conduct risk screenings more frequently. Lifestyle interventions to reduce the preventable risk factors of individuals should be developed and supported. Keywords: Diabetes, FINDRISC, Primary care, Adults, Score

Amaç: Diyabet son yıllarda sıklığı artan ciddi bir halk sağlığı sorunudur. Bu çalışmanın amacı birinci basamak sağlık kuruluşuna başvuran bireylerin diyabet risk skorlarının belirlenmesidir. Gereç yöntem: Tanımlayıcı- kesitsel tipte olan bu çalışma 01.12.2021-12.03.2022 tarihleri arasında 982 birey ile yürütülmüştür. Veriler sosyodemografik özellikler soru formu ve Fınnısh Diabetes Rısk Score (FINDRISC) anketi toplanmıştır. Diyabet risk skoru 15 puan ve üstü olanlar yüksek riskli olarak kabul edilmiştir. Bulgular: Çalışmaya katılan bireylerin yaş ortalaması 37.93±8.63 dir. Katılımcıların FINDRISC puan ortalaması 8.52±6.83 olup %22.8’i yüksek riskli grupta yer almaktadır. Çalışmada yer alan kadınlar, evli olanlar, düşük eğitim düzeyinde olanlar, düşük gelire sahip olanlar, BKI’sı yüksek olanlar, egzersiz yapmayanlar ve ailesinde diyabet öyküsü olanlar yüksek diyabet riskine sahiptir. Sonuç: Çalışmada yer alan yaklaşık her dört kişiden birinin yüksek riske sahip olduğu görülmektedir. Birinci basamak sağlık kuruluşlarının risk taramalarını daha sık yapmaları gerekmektedir. Bireylerin önlenebilir risk faktörlerini azaltılmasına yönelik yaşam tarzı müdahaleleri geliştirilmeli ve desteklenmelidir. Anahtar kelimeler: Diyabet, FINDRISC, birinci basamak, yetişkin, skor.
Birinci Basamak Sağlık Kuruluşuna Başvuran Yetişkinlerin Diyabet Risk Skorları: Kesitsel Bir Çalışma
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi